Evaluation of quality indicators of pectin-containing extracts of melons - S. Аzimova; M. Kizatova; G. Iskakova; Z. Uikassova (Алматы технологиялық университетінің хабаршысы, 2021)
The article investigated the analytical characteristics of pectin-containing extracts from pumpkin extracts of the "Karina" variety and melon of the "Torpeda" variety, their ability to form alkalis and complex. Based on the conducted experiments, pectins from melons are characterized by a low degree of esterification (34.7-36.8%), a high complexing capacity at the level of 240-290 mg Pb2+/g, which allows us to suggest the use of pectin products developed as natural detoxicants. On pectins of melon crops, the inverse relationship between the complexing abilities and the strength of the jelly was established.